Resultatives in Basque: A Diachronic Study - Krajewska, Dorota (Lingua Posnaniensis, 2013)
This paper deals with several aspects of the diachrony of Basque resultative constructions. In present day Basque, resultatives can be used with perfect-like meaning. The goal of this paper has been thus to study the development of the non-resultative uses of resultative constructions. To this end, the diathesis types of resultative and the meanings the construction may convey are studied in a corpus of 17th to 20th century texts. It has been found that in the time span covered by the study, new diathesis types are introduced and two new meanings develop: perfect and experiential.